Strengthening Community Program toward Healthy Ageing: What are the Potential Interventions? - Endang Mariani Rahayu; Nuri Purwito Adi; Levina Chandra Khoe (Amerta Nutrition, 2020)
Background: The number of elderly populations is increasing each year. As the number of elderly populations increases, the risk of non-communicable diseases, such as hypertension, diabetes, stroke, will also increase. The main risk factors for this disease include unhealthy diet, inadequate physical activity, smoking, inadequate rest, frequent stress and etc., which are considered as individual's lifestyle. This lifestyle starts when the individual grows up. Therefore, health interventions must be carried out since the individual turns to adulthood in order to prepare themselves for healthy ageing.Purpose: This study aimed to review the conceptual framework necessary to develop public health programs in preparation for healthy aging.Discussion: In the preparation for healthy ageing, health interventions should be conducted by targeting the adult population. The health interventions should be based on the theory of behavior change, life-course approach, and ecological approach. In addition, with the advancement of technology, the health interventions can also be carried out by involving digital intervention. The contextual elements, such as social, cultural and psychological context are also important in implementing the program so that it can be accepted by the targeted community.Conclusion: There is no intervention that fits all levels of society. Therefore, the interventions must be developed specifically for the population according to the local context.